Jewish Cemetery Association Strives to Create Comprehensive Graves Database - Feiler, Alan (Maryland Jewish Media, 2024)
With the help of volunteers, the Jewish Cemetery Association of Greater Baltimore is working to catalog the Jewish cemeteries and graves in the area for its digital database, including the identification of graves at some of Jewish Baltimore's oldest cemeteries.
Keywords: Comprehensive Jewish Graves Database; computer-vision processing; collaborative processing; Don Engel; UMBC Computer Science and Electrical Engineering Department; Jewish Cemetary Association